Screening vegetable crop species for resistance to Meloidogyne enterolobii - de Melo, Osvânder David; Maluf, Wilson Roberto; Gonçalves, Ranoel José de Sousa; Gonçalves Neto, Álvaro Carlos; Gomes, Luiz Antonio Augusto; Carvalho, Regis de Castro (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to identify genotypes of lettuce, sweet potato, bean, tomato, and Capsicum resistant to the nematode Meloidogyne enterolobii (Syn. M. mayaguensis), and to classify them according to their resistance degree. The following were evaluated: 10 genotypes of lettuce, 8 of sweet potato, 10 of bean and snap bean, 25 of Capsicum, and 6 of tomato genotypes. Reproduction factor and reproduction index were determined, and genotypes were classified according to their resistance degree to the nematode. Moderate levels of resistance were observed in the bean cultivar Aporé and in the accessions of pepper BGH-433 and BGH-4285, and of sweet pepper, PIM-031, PIX-022I-31-07-02, and PIX-022I-31-13-01. All tomato genotypes are susceptible to M. enterolobii. Lettuce cultivars Julia, Hortência, Verônica, Grand Rapids and Babá de Verão, and sweetpotato clones UFLA07-49 and UFLA07-53 are very resistant to the nematode. Apparently, the resistance to M. enterolobii is controlled by different genes from the ones which confer resistance to other species and races of Meloidogyne.